Cu and Zn in soils under concentrated feeding animal operations. Córdoba. Argentina - Bécher Quinodóz, Fátima Noelia (2016)
The Colacha stream basin (Córdoba, Argentina) is an agro-ecosystem where intensive livestock production exists. Protein complexes supplied to animals incorporate heavy metals into the environment through faeces and urine. In order to determine the presence and behavior of heavy metals (Cu and Zn) in soils located under concentrated animal feed operation (CAFOs), three soil profiles were surveyed according to livestock activities a) medium cow CAFO b) small pig CAFO c) natural soil (reference). The results were treated with multivariate descriptive statistics techniques. The soil profiles under CAFOs, presented maximum Cu and Zn values of 34.37 ppm and 43.31 ppm, respectively. These values are in the range of the average concentration of soils worldwide, although they showed a notorious increase compared to the background regional soil values (Cu = 7.31 ppm and Zn = 11.67 ppm) that is, an increment of 470% and 370% respectively. The results and multivariate statistical analysis indicate that Cu and Zn in available state and complexed with organic matter (OM) are controlled by pH and OM values. In the most disturbed soil profile (medium CAFO) there is more OM and total Cu and Zn values are most clearly associated with it. The results show the impact of livestock on soil, which could be a source of pollutants wherein eventually would trigger their migration to the water tabl.